Detection of Apple Hammerhead Viroid, Apple Luteovirus 1 and Citrus Concave Gum-Associated Virus in Apple Propagation Materials and Orchards in the Czech Republic and Hungary - Várallyay, Eva; Přibylová, Jaroslava; Galbacs, Zsuzsanna Nagyne; Jahan, Almash; Varga, Tunde; Špak, Josef; Lenz, Ondřej; Fránová, Jana; Sedlák, Jiří; Koloniuk, Igor (Viruses, 2022)
Grafting cultivars onto rootstocks is a widely used practice by the apple industry predominantly aimed at faster fruit bearing. Using high-throughput sequencing, we revealed the presence of recently described viral agents, namely apple hammerhead viroid (AHVd), apple luteovirus 1 (ALV-1), and citrus concave gum-associated virus (CCGaV), in germplasm collections and production orchards in the Czech Republic and Hungary. The HTS results were validated with RT-(q)PCR, and Northern blotting techniques. To obtain further insight about the presence of these agents, RT-PCR based surveys were carried out and showed their widespread presence alone or in mixed infections. The pathogens were present both in production areas and in feral samples. In addition, rootstock-to-scion transmission of ALV-1 and CCGaV was confirmed using commercial rootstock materials. Phylogenetic relationships based on partial sequences of distinct variants were also investigated. Furthermore, the rosy apple aphid was found to be ALV-1-positive, suggesting that it might be a potential vector of the virus.
Keywords: transmission; HTS; satelitní viry; Phylogeny; aphid; Luteovirus; viroidy; apple; Hungary; Maďarsko; viroid; virus; Viroids; fylogeneze; Satellite Viruses; Czech Republic; Citrus; rootstock; Česká republika